EVOLUTIONARY CHANGES OF THE KINEMATICS OF THEGALACTIC THIN DISK STARS IN THE SOLAR NEIGHBORHOOD - Koval, V. V.; Borkova, T. V.; Marsakov, V. A. (Одеські астрономічні публікації, 2008)
According to the data of Nordstrom et al. (2004) catalog is carried out the comparative analysis of the velocity ellipsoid parameters of the galactic disk stars of different metallicity and the character of their change from the age is investigated. It is shown, that dispersions of all three components of spatial velocities increase with age, submitting to the power law σ i≈ t0.26 , i. e., exponent proved to be beyond the ranges of errors less than previously usually obtained It is discovered a difference in the values of the semiaxes of velocity ellipsoids between stars with the metallicity more and less [Fe/H] ≈ -0.3, which can evidences about a difference in the dynamic state of the matter, from which they were formed. It is established that the form of the velocity ellipsoids of the stars of different metallicity in the course of time does not change - ellipsoid simply increases in the sizes and is turned. After exception of the stars of the moving groups the character of dependences on the age of the velocity ellipsoids parameters did not undergo the significant changes.